Development and validation of a hurricane nature run using the joint OSSE nature run and the WRF model - David S. Nolan; Robert Atlas; Kieran T. Bhatia; Lisa R. Bucci (Journal of Advances in Modeling Earth Systems, 2013)
A nature run is a critical component of an observing system simulation experiment (OSSE), which is a framework for evaluating the potential impact of additional observations, enhanced observing systems, or alternative data assimilation schemes toward improving numerical weather forecasts. The nature run is a period of simulated weather generated by a research‐quality numerical model, from which synthetic observations are sampled and provided to the data assimilation system and forecast model. This paper describes the development and validation of a nature run that depicts the life cycle of a strong hurricane over the North Atlantic Ocean. For compatibility with related research projects, the hurricane nature run is generated by a regional model, the weather research and forecasting model (WRF), embedded within the Joint OSSE global nature run previously generated by the European Center for Medium‐Range Weather Forecasting. The domain sizes, resolution, and physical parameterizations used in the WRF simulation are discussed, and the evolution of the storm from tropical wave to recurving hurricane is described. The realism of the simulated hurricane is evaluated by comparing the model output to composited data from real hurricanes obtained from both in situ and remotely sensed observations. These include the pressure‐wind relationship, the kinematic and thermodynamic structure of the boundary layer, the size and outward slope of the radius of maximum winds, and contours of frequency by altitude diagrams of reflectivity and vertical velocity. The strengths and weaknesses of the nature run hurricane are discussed.